Comprehensive analysis of circular RNA expression profiles in cisplatin-resistant non-small cell lung cancer cell lines. (27th July 2020) - Song, Lin; Cui, Zhilei; Guo, Xuejun
Abstract: Platinum-based drugs such as cisplatin are widely used in combination chemotherapy for non-small cell lung cancer (NSCLC) owing to their high clinical response rate; however, acquired resistance to cisplatin is eventually inevitable. Circular RNAs (circRNAs) are involved in the development of diverse types of cancers, but their connection to cisplatin-resistance in NSCLC has not been studied. In the present study, two cisplatin-resistant NSCLC cell lines (A549/DDP and PC9/DDP) were established by gradually increasing concentrations of cisplatin in the media. The resulting cell lines possessed high resistance to cisplatin and strong proliferation, migration, and colony formation abilities compared to the parental cells. Microarray analysis identified 19, 161 circRNAs that were dysregulated in cisplatin-resistant cell lines (fold change abs>2), including 11, 915 up-regulated and 7246 down-regulated circRNAs. The expression of the top five up-regulated and down-regulated circRNAs was validated using real-time quantitative polymerase chain reaction. A circRNA–micro RNA (miRNA) network of the top 20 dysregulated circRNAs and their predicted miRNAs was constructed using Cytoscape. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses revealed that the host genes of the identified circRNAs were involved in the regulation of MAP kinase kinase kinase kinase activity, 6-phosphofructo-2-kinase activity, focal adhesion, ErbB signaling, and ECM-receptor interactions, which may contribute to cisplatin resistance in NSCLC. In summary, this is the first report on circRNA profiling in cisplatin-resistant NSCLC cells and it provides new potential targets for the reversal of cisplatin resistance in NSCLC.